How inequality drives growth : an investigation of the transmission channels for OECD countries - Coelho, José Carlos (2021)
This paper assesses the relationship between inequality and growth for 34 advanced OECD countries between 1990 and 2019 using recent Gini coefficients from Solt (2020) database and through a dynamic panel technique of two-step system GMM (Generalized Method of Moments). We find that the Gini coefficient of disposable income has a positive and significant impact, at a 10% level of significance, on subsequent economic growth over the five-year period. This result is explained based on the fiscal policy and saving channels, and also through the role of investment. More specifically, inequality translates into lower shares of public consumption and direct taxation on GDP, which boosts economic growth. Furthermore, inequality encourages saving and stimulates investment, which results in greater growth of the income per capita level.